The Strategic Role of Religion in Shaping Social Values and Social Stability in the Modern Era - Widyawati, Ririn (Maliki Interdisciplinary Journal, 2026)
Religion is a belief system that plays a vital role in human life, both as a spiritual guide and as a regulator of social life. Religion serves to shape societal values, norms, and behavior through moral teachings such as honesty, responsibility, tolerance, and social awareness. In social life, religion serves as a guide to life, a tool of social control, a unifying force, a source of motivation, and a means of developing individual character. Furthermore, religion also has educational, integrative, and transformative functions, as well as fostering social identity, supporting a harmonious and civilized social life. In the modern era, religion faces various challenges, such as globalization, technological and social media developments, increasing individualism and materialism, and a lack of in-depth religious understanding. These challenges can impact the application of religious values ​​in daily life. Therefore, strengthening religious education, improving digital literacy, and fostering the role of families and communities in instilling religious values ​​are necessary to ensure their relevance in the face of changing times. Thus, religion can continue to serve as a moral and spiritual foundation for building a peaceful and prosperous society.